Accuracy bounds and measurements of a contactless permittivity sensor for gases using synchronized low-cost mm-wave frequency modulated continuous wave radar transceivers - Och, Andreas; Schrattenecker, Jochen O.; Schuster, Stefan; Hölzl, Patrick A.; Freidl, Philipp F.; Scheiblhofer, Stefan; Zankl, Dominik; Weigel, Robert (Sensors, 2019)
A primary concern in a multitude of industrial processes is the precise monitoring of gaseous substances to ensure proper operating conditions. However, many traditional technologies are not suitable for operation under harsh environmental conditions. Radar-based time-of-flight permittivity measurements have been proposed as alternative but suffer from high cost and limited accuracy in highly cluttered industrial plants. This paper examines the performance limits of low-cost frequency-modulated continuous-wave (FMCW) radar sensors for permittivity measurements. First, the accuracy limits are investigated theoretically and the Cramér-Rao lower bounds for time-of-flight based permittivity and concentration measurements are derived. In addition, Monte-Carlo simulations are carried out to validate the analytical solutions. The capabilities of the measurement concept are then demonstrated with different binary gas mixtures of Helium and Carbon Dioxide in air. A low-cost time-of-flight sensor based on two synchronized fully-integrated millimeter-wave (MMW) radar transceivers is developed and evaluated. A method to compensate systematic deviations caused by the measurement setup is proposed and implemented. The theoretical discussion underlines the necessity of exploiting the information contained in the signal phase to achieve the desired accuracy. Results of various permittivity and gas concentration measurements are in good accordance to reference sensors and measurements with a commercial vector network analyzer (VNA). In conclusion, the proposed radar-based low-cost sensor solution shows promising performance for the intended use in demanding industrial applications.
CRIS-Team Scopus Importer:2019-08-20
Keywords: Cramér-Rao bounds; Gas detectors; Millimeter wave radar; Permittivity; Phase estimation; Radar measurements; Time of arrival estimation